Electronic and steric effects in the control of the Anilinium chloride catalyzed condensation reaction between Aldones and 4-Phenylthiosemicarbazide - Kasséhin, Urbain C.; Gbaguidi, A. Fernand; Kapanda, Coco N.; McCurdy, Christopher R.; Bigot, André K.; Poupaert, Jacques H. (My University, 2013)
A concise series of aldehydes and ketones were reacted in a condensation reaction with 4phenylthiosemicarbazide in order to assess the relative influence of the steric and electronic effects in the control of this reaction. While steric effects had a modest impact, electronic effects and in particular the mesomeric donating effect delivered by a phenyl ring produced a strong passivating influence on the reactivity of these aldones. Additionally, the cyclopropyl substituent totally passivated the reaction via the interfering factor of its inherent sigma-aromaticity. When reacted with cyclopropyl-phenylketone, under our standard conditions, 4-phenylthiosemicarbazide gave in 82%, an original 1, 4-dihydrotetrazine via a double consecutive self-condensation.
Keywords: Thiosemicarbazone; electronic effect; steric effect; ion catalysis aniline; sigma; aromaticity